Urgensi Open Government Melalui Inisiatif Open Data dalam Mencegah Korupsi Anggaran Penanganan Covid-19 di Indonesia - Dimas Aufar Dwi Cahya; Janwan Sri Rejekinta Tarigan; Tomy Rivaldo (Journal of Governance Innovation, 2021)
This article explains the process of managing Covid-19 funds in several regions in Indonesia. Using the grand theory of open government and qualitative approaches to the type of literature study research, researchers conducted data collection to be able to explain the importance of using Open Government through open data initiatives in order to manage the Covid-19 budget and avoid potential corruption. The Covid-19 pandemic that has hit Indonesia since the beginning of March 2020, has directly encouraged several local governments to be able to act quickly to deal with the spread of the virus before increasing. Some areas were detected as the main points of the spread of the virus which was marked by the increasing number of corona virus sufferers becoming the center of attention of the researchers, especially in relation to the handling budget of Covid-19 which automatically participated to swell. From the analysis of data that has been done, it shows that some regions that experienced a surge in corona virus sufferers accompanied by swelling of the Covid-19 budget, apparently did not include a clear budget management process. Some regions were found to only focus on efforts to reduce the virus distribution statistics, without giving serious attention to transparency, openness, and accountability in managing co-19 budget management. Artikel ini menjelaskan permasalahan tata kelola angaran Covid-19 di beberapa daerah di Indonesia. Menggunakan grand theory open government dan pendekatan kualitatif dengan tipe penelitian studi literatur, peneliti melakukan pengumpulan data sekunder untuk dapat menjelaskan pentingnya penggunaan open government melalui inisiatif open data dalam mengelola anggaran Covid-19 demi menghindari potensi korupsi. Pandemi Covid-19 yang telah melanda Indonesia sejak awal Maret 2020, telah secara langsung mendorong beberapa pemerintah daerah untuk dapat bertindak cepat melakukan penanganan sebelum persebaran virus semakin meningkat. Beberapa daerah terdeteksi menjadi titik utama persebaran virus yang ditandai dengan meningkatnya angka penderita virus corona menjadi pusat perhatian peneliti, terutama kaitannya dengan anggaran penanganan Covid-19 yang secara otomatis turut serta membengkak. Dari analisis data yang telah dilakukan, menunjukkan bahwa beberapa daerah yang mengalami lonjakan penderita virus corona disertai dengan pembengkakan anggaran penanganan Covid-19, ternyata tidak mengikutsertakan proses pengelolaan anggaran yang jelas. Beberapa daerah kedapatan hanya berfokus pada upaya menurunkan statistik persebaran virus, tanpa memberikan perhatian serius pada transparansi, keterbukaan, dan akuntabilitas pengelolaan anggaran penanganan covid-19.